Granule Dendrobii suppresses chronic atrophic gastritis induced by N-methyl-N’-nitro-N-nitrosoguanidine by modulating the gastrointestinal bacteria in rats: Granule Dendrobii suppresses chronic atrophic gastritis - Xi, Caicai; Feng, Kang; Chen, Xuan; Wu, Hao; Chen, Hongshan; Huang, Hui; Ren, Zeming; Dai, Guanhai; Xue, Xiaomin; Zhou, Huifang; Lu, Zhenmei; Wu, Renzhao (Cellular and Molecular Biology, 2023)
Chronic atrophic gastritis (CAG) is an important stage in the transformation of the normal gastric mucosa into gastric cancer. Granule Dendrobii (GD), a proprietary Chinese medicine, has proven clinical efficacy in treating CAG. GD might promote the reversal of precancerous lesions by improving them in CAG patients. However, the mechanism of GD in CAG treatment is relatively less understood. Here, N-methyl-N’-nitro-N-nitrosoguanidine (MNNG)-induced CAG rats were treated with GD and its efficacy was evaluated by observing the changes in the rats’ weight and the pathology of gastric tissues. The potential effect of GD on the bacteria was predicted and verified in the large and small intestines and stomachs of CAG rats using amplicon sequencing and RT-qPCR. The results showed that GD could ameliorate the symptoms of body weight loss in CAG rats. Hematoxylin-Eosin (HE) and Alcian Blue (AB) staining showed that GD significantly improved the pathological state of the gastric mucosa in CAG rats. The relative abundance (RA) of Lactobacillus and Turicibacter significantly decreased after GD intervention compared with that of the model group (P < 0.05), indicating that GD might improve CAG by regulating the RA of Lactobacillus and Turicibacter. These findings revealed that Lactobacillus and Turicibacter as bacteria agents associated with gastritis, have the potential to inhibit gastric cancer, especially Turicibacter maybe another pathogen of CAG besides Helicobacter pylori (HP), which is worthy of further study. Meanwhile, the findings provided new ideas and materials for the research and development of new CAG drugs.